2019
DOI: 10.3171/2018.3.jns1866
|View full text |Cite
|
Sign up to set email alerts
|

Noncontrast vestibular schwannoma surveillance imaging including an MR cisternographic sequence: is there a need for postcontrast imaging?

Abstract: OBJECTIVE The purpose of this study was to evaluate the use of a noncontrast MRI protocol that includes a cisternographic sequence (CISS/FIESTA/3D DRIVE) compared to a protocol that includes a gadolinium-enhanced sequence in order to determine whether a noncontrast approach could be utilized to follow vestibular schwannomas. METHODS A total of 251 patients with vestibular schwannomas who underwent MRI of the temporal bones that included both cisternographic sequence and postcontrast T1 imaging between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Accuracy when utilizing T2WI was best within the posterior fossa on our study, as compared to along the convexities, as previously reported 13 . This may be attributed to the ease of measuring a soft tissue mass in the basilar cisterns where abundance of CSF (cerebrospinal fluid) provides excellent imaging contrast, as has been demonstrated in the imaging assessment of intracranial schwannomas 11 …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Accuracy when utilizing T2WI was best within the posterior fossa on our study, as compared to along the convexities, as previously reported 13 . This may be attributed to the ease of measuring a soft tissue mass in the basilar cisterns where abundance of CSF (cerebrospinal fluid) provides excellent imaging contrast, as has been demonstrated in the imaging assessment of intracranial schwannomas 11 …”
Section: Discussionsupporting
confidence: 79%
“…In 2018, a retrospective case series of 251 patients with vestibular schwannomas demonstrated no significant difference in surveilled size using a noncontrast "cisternographic" technique. 11 A similar study found noncontrast MR surveillance technique performance comparable to contrast MR for detection of subependymal giant cell astrocytomas in tuberous sclerosis complex. 12 In 2020, He et al reported no significant difference in surveilled size of a case series of 18 supratentorial cerebral convexity meningiomas when replacing GBCA-enhanced studies with 2D spin echo T2-weighted images (TWIs) and fluid-attenuated inversion recovery (FLAIR) sequences.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…1,2,[9][10][11][12] Our findings are similar to those in other previous studies that have demonstrated the benefits of adding bSSFP sequences to standard neuroimaging protocols for CNS tumor detection, including high accuracy for vestibular schwannoma detection and spinal drop metastases. 4,[13][14][15][16] Although the inclusion of a bSSFP sequence increased the total scan length by 6 minutes on average, we found that the improved sensitivity and confidence in the interpretation justify the additional imaging time. Furthermore, there is diagnostic synergy between the bSSFP and the standard MR images when interpreted in conjunction.…”
Section: Discussionmentioning
confidence: 99%
“…MPR is particularly useful for delineating compressive phenomena, such as mass effects exerted on adjacent neural structures. 15 We previously reported on this approach, demonstrating utility of MPR for characterizing vascular loops features (e.g., position, contact with nerve, and vessel caliber). MPR findings have previously been correlated with auditory and vestibular symptoms 16 and discriminate benign nerve displacement from compressive nerve injury for surgical planning.…”
Section: Introductionmentioning
confidence: 99%